Barb Wilson letter to Robert Myers regarding Spring report, June 2, 1986 - Wilson, Barbara L.et al (1986)
Letter from Barb Wilson to Robert Myers dated June 2, 1986. In this letter Wilson talks about rescuing a fledgling Kestrel, the weather and spring migration. Letter includes an annotated list of birds sighted. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1986. Epson - sheet feed/flatbed